Flavonoids as Immunoregulators: Molecular Mechanisms in Regulating Immune Cells and Their Therapeutic Applications in Inflammatory Diseases - Liu, Yingshu; Jiao, Ao (Frontiers in Immunology, 2025)
Flavonoids are a vital class of dietary polyphenolic compounds that have attracted considerable attention owing to their powerful immunoregulatory and anti-inflammatory effects. This review summarizes recent advances in understanding the role of flavonoids in regulating immune cells and their therapeutic application in inflammatory diseases. We present an overview of the definition, classification, and dietary sources of flavonoids and detail their regulatory effects on multiple key immune cells, therapeutic potential of flavonoids in various inflammatory diseases, as well as discuss strategies to improve their bioavailability and targeting. Despite the promising immunoregulatory properties of flavonoids, their clinical utilization is impeded by issues such as low bioavailability, considerable interindividual variability, and the absence of high-quality randomized controlled trials. Future research needs to focus on elucidating the precise mechanisms of flavonoids, optimizing their pharmacokinetic properties, and conducting more standardized clinical trials to facilitate the transformation of these natural compounds into standardized immunomodulatory therapeutic agents.